Willingness To Pay For mHealth Application: The Relationship Between Attitude, Social Influence And Self-Efficacy With The Moderating Effect Of Initial Trust - Seman, Sharidatul Akma Abu (2020)
Willingness To Pay For mHealth Application: The Relationship Between Attitude, Social Influence And Self-Efficacy With The Moderating Effect Of Initial Trust